The sands are running out - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
The Hartley Sand Trap could mean the end to the curse of sand blocking up filters and irrigation pipes. This simple invention developed and patented by Tim Hartley is worth the while for any farmer or farmers group involved in irrigation. It...